Transcriptome and Proteome of Fish-Pathogenic Streptococcus agalactiae Are Modulated by Temperature - Tavares, Guilherme C.; Carvalho, Alex F.; Pereira, Felipe L.; Rezende, Cristiana P.; Azevedo, Vasco A. C.; Leal, Carlos A. G.; Figueiredo, Henrique C. P. (Frontiers in Microbiology, 2018)
Streptococcus agalactiae is one of the most important pathogens associated with streptococcosis outbreaks in Nile tilapia farms worldwide. High water temperature (above 27°C) has been described as a predisposing factor for the disease in fish. At low temperatures (below 25°C), fish mortalities are not usually observed in farms. Temperature variation can modulate the expression of genes and proteins involved in metabolism, adaptation, and bacterial pathogenicity, thus increasing or decreasing the ability to infect the host. This study aimed to evaluate the transcriptome and proteome of a fish-pathogenic S. agalactiae strain SA53 subjected to in vitro growth at different temperatures using a microarray and label-free shotgun LC-HDMSE approach. Biological triplicates of isolates were cultured in BHIT broth at 22°C or 32°C for RNA and protein isolation and submitted for transcriptomic and proteomic analyses. In total, 1,730 transcripts were identified in SA53, with 107 genes being differentially expressed between the temperatures evaluated. A higher number of genes related to metabolism, mainly from the phosphotransferase system (PTS) and ATP-binding cassette (ABC) transport system, were upregulated at 32°C. In the proteome analysis, 1,046 proteins were identified in SA53, of which 81 were differentially regulated between 22ºC and 32ºC. Proteins involved in defense mechanisms, lipid transport and metabolism, and nucleotide transport and metabolism were upregulated at 32ºC. A higher number of interactions were observed in proteins involved in nucleotide transport and metabolism. We observed a low correlation between the transcriptome and proteome datasets. Our study indicates that the transcriptome and proteome of a fish-adapted S. agalactiae strain are modulated by temperature, particularly showing differential expression of genes/proteins involved in metabolism, virulence factors and adaptation.